The Influence of Community Behavior on the Incident of Malaria in the Working Area of Larat Health Center, North Tanimbar District, Tanimbar Islands - Abigael Laritmas; Yuly Peristiowati; Prima Dewi Kusumawati (STRADA : Jurnal Ilmiah Kesehatan, 2026)
Malaria is one of the top 10 diseases that is still a health problem that has occurred for 3 consecutive years in the Larat Health Center working area. The aim of this research is to analyze the influence of behavior. Community regarding the incidence of malaria in the working area of ​​the Larat Community Health Center, North Tanimbar District. This research is quantitative in approach cross sectional. The sampling technique uses random sampling with all malaria sufferers and some people who are not malaria sufferers in malaria-prone areas in the Larat Community Health Center working area as many as 372 people.